Salivary gland transcriptomes and proteomes of Phlebotomus tobbi and Phlebotomus sergenti, vectors of leishmaniasis. - Iva Rohoušová; Sreenath Subrahmanyam; Věra Volfová; Jianbing Mu; Petr Volf; Jesus G Valenzuela; Ryan C Jochim (Public Library of Science (PLoS), 2012)
Background Phlebotomus tobbi is a vector of Leishmania infantum, and P. sergenti is a vector of Leishmania tropica. Le. infantum and Le. tropica typically cause visceral or cutaneous leishmaniasis, respectively, but Le. infantum strains transmitted by P. tobbi can cause cutaneous disease. To better understand the components and possible implications of sand fly saliva in leishmaniasis, the transcriptomes of the salivary glands (SGs) of these two sand fly species were sequenced, characterized and compared. Methodology/principal findings cDNA libraries of P. tobbi and P. sergenti female SGs were constructed, sequenced, and analyzed. Clones (1,152) were randomly picked from each library, producing 1,142 high-quality sequences from P. tobbi and 1,090 from P. sergenti. The most abundant, secreted putative proteins were categorized as antigen 5-related proteins, apyrases, hyaluronidases, D7-related and PpSP15-like proteins, ParSP25-like proteins, PpSP32-like proteins, yellow-related proteins, the 33-kDa salivary proteins, and the 41.9-kDa superfamily of proteins. Phylogenetic analyses and multiple sequence alignments of putative proteins were used to elucidate molecular evolution and describe conserved domains, active sites, and catalytic residues. Proteomic analyses of P. tobbi and P. sergenti SGs were used to confirm the identification of 35 full-length sequences (18 in P. tobbi and 17 in P. sergenti). To bridge transcriptomics with biology P. tobbi antigens, glycoproteins, and hyaluronidase activity was characterized. Conclusions This analysis of P. sergenti is the first description of the subgenus Paraphlebotomus salivary components. The investigation of the subgenus Larroussius sand fly P. tobbi expands the repertoire of salivary proteins in vectors of Le. infantum. Although P. tobbi transmits a cutaneous form of leishmaniasis, its salivary proteins are most similar to other Larroussius subgenus species transmitting visceral leishmaniasis. These transcriptomic and proteomic analyses provide a better understanding of sand fly salivary proteins across species and subgenera that will be vital in vector-pathogen and vector-host research.